Legitimacy as the sign of the right - I. L. Chestnov (Теоретическая и прикладная юриспруденция)
Legitimacy constructed and constituts society, including the right to. Here possible conclusion, that legitimacy is the feature of the law. However not all agree with this point. For representatives of legal positivism, as for jus natural supporters legitimacy is not the feature of the law. Classical law sociology stand legitimacy as feature of the law, but not takes her power, constructed by nature. From post-classical methodology point, Features of law are human proportionality, iconic mediation, construction of law, the contextual and Dialogic of law. All of this features assume the legitimacy as their content. Legitimacy as recognition of the rule of law is a condition of its existence.